Deciphering Consumer Choices: Axioo Brand Laptop Purchase Patterns at AFA Computer Ambarawa - Anastasia Fransiska Sihura; Ray Octafian (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
In the current context, businesses must effectively utilize their resources, including the implementation of strategies aimed at influencing consumer buying choices, particularly for Axioo brand laptops. This research aims to explore consumers' perceptions of their decision-making process when considering the purchase of an Axioo brand laptop and identify strategies to enhance the purchase decision-making process for this brand. The research employs a descriptive qualitative methodology.The findings of this study reveal that consumers' purchasing decisions regarding Axioo laptops are influenced by factors such as performance, specifications, pricing, and ease of use. Additionally, the availability of various color options and the compact design of Axioo laptops contribute to their appeal. To enhance the purchase decisions for Axioo brand laptops, effective strategies are needed to capture consumers' interest. These strategies may include promotional campaigns, incentive offerings, and the utilization of social media as a powerful promotional tool, all of which can significantly impact and bolster purchase decisions.